2019
DOI: 10.1111/jcmm.14540
|View full text |Cite
|
Sign up to set email alerts
|

Zingerone attenuates aortic banding‐induced cardiac remodelling via activating the eNOS/Nrf2 pathway

Abstract: Cardiac remodelling refers to a series of changes in the size, shape, wall thickness and tissue structure of the ventricle because of myocardial injury or increased pressure load. Studies have shown that cardiac remodelling plays a significant role in the development of heart failure. Zingerone, a monomer component extracted from ginger, has been proven to possess various properties including antioxidant, anti‐inflammatory, anticancer and antidiabetic properties. As oxidative stress and inflammation contribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…However, LA pretreatment increased eNOS but not iNOS or nNOS levels. Our previous study suggested that eNOS/Nrf2 pathway regulates pressure overload-induced cardiac remodeling (Liu et al, 2019). In addition, previous studies reported that the transcription activity of Nrf2 depends largely on the nuclear translocation of Nrf2 (Silva-Islas and Maldonado, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…However, LA pretreatment increased eNOS but not iNOS or nNOS levels. Our previous study suggested that eNOS/Nrf2 pathway regulates pressure overload-induced cardiac remodeling (Liu et al, 2019). In addition, previous studies reported that the transcription activity of Nrf2 depends largely on the nuclear translocation of Nrf2 (Silva-Islas and Maldonado, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Excessive ROS accumulation has been associated with a progression to cardiac fibrosis and end‐stage heart failure 12,13,42,43 . Targeting oxidative stress has been the subject of investigation in the preclinical setting and demonstrated highly promising results 44‐46 . As a bioactive natural compound, TQ is one of the agents that has been considered as potent antioxidants and has been extensively studied in the past decade.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al. (2019) found that intragastric administration of zingerone to mice for 28 days at a dose of 10 or 20 mg kg −1 day −1 decreased the infiltration of CD68 positive macrophages. Zingerone is known to have potent pharmacological activities including antioxidant and anti‐inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%